Torneamento de Inconel 718 com aplicação de lubrificantes sólidos - Marques, Armando (2015)
The nickel-based superalloys have a high mechanical strength which remains at elevated temperature, high creep and fatigue resistances and excellent oxidation resistance. This makes these alloys highly recommended for use in high temperature working environments such as mechanical components for the aerospace industry. However, these characteristics are major problems when machining them, as it promotes high heat generation in the flow zone, resulting in the development of high wear rates on the cutting tools. In order to reduce the problems caused by the high temperatures generated, the application of a cutting fluid, when possible, is essential to reduce friction at the chip-tool-workpiece interfaces and lower the temperatures in the cutting zone. Seeking to further increase in the efficiency of cutting fluids during machining of nickel alloys, this work presents a study of the influence of solid lubricants, graphite and molybdenum disulphide (MoS2) mixed to a vegetal based cutting fluid, applied by conventional method (flooding) and minimal quantity of fluid - MQF in turning of Inconel 718 with carbide and ceramic (mixed, whisker and SiAlON) tools. When turning with cemented carbide tools the addition of graphite to the cutting fluid provided the best results, while with ceramic tools MoS2 presented the best performance. The life of the carbide tool had an average increase above 200% in conventional flooding application of cutting fluid when compared to MQF, regardless the addition of solid lubricant. The addition of solid lubricants promoted an increase in the life of whisker and SiAlON tools. The flank wear was dominant for cemented carbide tools and SiAlON ceramics, while for whisker and mixed ceramics the notch wear was predominant. Attrition and diffusion wear mechanism were observed in all evaluated conditions. The addition of solid lubricant to the cutting fluid provided significant improvements in the surface roughness values for most of the evaluated conditions. However, there were no significant changes in the machining forces and cutting temperature. The residual stress was tensile and compression, depending on the fluid application method. Overall, the addition of solid lubricant showed no significant differences.